Cleaning of lead smelting flue gas scrubber sludge and recovery of lead, selenium and mercury by the hydrometallurgical route. Issue 11 (3rd June 2018) - Xing, Peng; Ma, Baozhong; Wang, Chengyan; Chen, Yongqiang
ABSTRACT: The expansion of the nonferrous metal smelting industry in the recent two decades has resulted in the generation of massive quantities of flue gas scrubber sludge containing hazardous heavy metals, such as cadmium, lead, arsenic, selenium and mercury (Hg), posing a potential environmental threat. In this work, lead smelting flue gas scrubber sludge was treated by a hydrometallurgical process to achieve sludge cleaning and economic recovery of metal values lead, selenium and mercury. The sludge was preliminarily leached by sodium chloride solution to extract lead. Under the optimum conditions, 99.8% of lead was selectively leached into the solution and subsequently precipitated by calcium oxide while almost the entire selenium and mercury remained in residue. Ninety-eight percent of selenium and 99.8% of mercury were further leached by hydrochloric acid solution with sodium chlorate. 99.3% of mercury was precipitated as red mercuric oxide from the Se–Hg leach liquor by adding sodium hydroxide. After the mercury was removed from the solution, 97.5% of selenium was reduced and precipitated as crude selenium by reduction with sodium sulfite. Recovery yields of lead, mercury and selenium by this process were 99.6%, 98.9% and 95.5%, respectively.